Activités tertiaires et hiérarchies urbaines : une évaluation de six méthodes d’analyse - Ouellet, Normand; Polèse, Mario (L'Actualité économique)

(untitled) (HEC Montréal, 1977)
AbstractUrban and regional economists are often asked to construct central place models which will properly describe the urban hierarchy (in terms of the service sector) of the region which they are studying. In all such studies, the chief analytical problem is basically one of correctly defining (and measuring) tertiary activity and of correctly weighting the various functions which make up the service sector.In this paper, the authors review six alternative methods for measuring and weighting tertiary functions. The mathematical and conceptual properties of each approach are discussed and evaluated. In the second part of the article, the authors compare the actual results obtained by these alternative methods, using data on the Quebec urban system to test their results. They conclude that no one method is entirely satisfactory, each approach measuring a part of reality. But some methods do nevertheless seem to perform better than others: in this respect, the use of localization coefficient type approach seems generally to give the least biased results.